Вынесите общий множетель за скобки
a(b-c)+ 10 (b-c)
7(a+x)- b(a+x)
c (x-y)- (x-y)
a(x-y)-(x-y)
(a-b)^2+3 (a-b)
(x-1)^2+7 (x-1)
(b+5)^2-b (b+5)
-2a (a+4)+ (a+4)^2

2
Комментарий удален
Комментарий удален
Комментарий удален
да с утра
хорошо

Ответы и объяснения

  • Bernard14
  • почетный грамотей
2013-12-26T20:33:59+00:00
a(b-c)+ 10 (b-c)=(b-c)*(a+10)
7(a+x)- b(a+x)=(a+x)*(7-b)
c (x-y)- (x-y)=(x-y)*(c-1)
a(x-y)-(x-y)=(x-y)*(a-1)
(a-b)^2+3 (a-b)=(a-b)*(a-b+3)
(x-1)^2+7 (x-1)=(x-1)*(x+6)
(b+5)^2-b (b+5)=(b+5)*5
-2a (a+4)+ (a+4)^2=(a+4)*(4-a)

2013-12-26T20:36:30+00:00